Desain Beam Shaping Assembly (BSA) berbasis D-D Neutron Generator 2,45 MeV untuk Uji Fasilitas BNCT - Desman P. Gulo; Suryasatriya T.; Slamet Santosa; Y. Sardjono (Department of Physics, Sebelas Maret University, 2015)
Boron Neutron Capture Therapy (BNCT) is one of the cancer treatments that are being developed in nowadays. In order to support BNCT treatment for cancer that exists in underneath skin like breast cancer, the facility needs a generator that is able to produce epithermal neutron. One of the generator that is able to produce neutron is D-D neutron generator with 2.45 MeV energy. Based on the calculation of this paper, we found that the total production of neutron per second (neutron yield) from Neutron Generator (NG) by PSTA-BATAN Yogyakarta is 2.55×1011 n/s. The energy and flux that we found is in the range of quick neutron. Thus, it needs to be moderated to the level of epithermal neutron which is located in the interval energy of 1 eV to 10 KeV with 109 n/cm2s flux. This number is the recommendation standard from IAEA. Beam Shaping Assembly (BSA) is needed in order to moderate the quick neutron to the level of epithermal neutron. One part of BSA that has the responsibility in moderating the quick neutron to epithermal neutron is the moderator. The substance of moderator used in this paper is MgF2 and A1F3. The thickness of moderator has been set in in such a way by using MCNPX software in order to fulfill the standard of IAEA. As the result of optimizing BSA moderator, the data obtain epithermal flux with the total number of 4.64×108 n/cm2/s for both of moderators with the thickness of moderator up to 15 cm. At the end of this research, the number of epithermal flux does not follow the standard of IAEA. This is because the flux neutron that is being produced by NG is relatively small. In conclusion, the NG from PSTA-BATAN Yogyakarta is not ready to be used for the BNCT treatment facility for the underneath skin cancer like breast cancer.